Guidelines for Parkinson’s disease treatment: consensus from the Movement Disorders Scientific Department of the Brazilian Academy of Neurology - motor symptoms - Saba, Roberta Arb; Maia, Débora Palma; Cardoso, Francisco Eduardo Costa; Borges, Vanderci; F. Andrade, Luiz Augusto; Ferraz, Henrique Ballalai; Barbosa, Egberto Reis; Rieder, Carlos Roberto de Mello; Silva, Delson José da; Chien, Hsin Fen; Capato, Tamine; Rosso, Ana Lúcia; Souza, Carlos Frederico Lima; Bezerra, José Marcelo Ferreia; Nicaretta, Denise; Barsottini, Orlando Graziani Povoas; Godeiro-Júnior, Clécio; Barcelos, Lorena Broseghini; Cury, Rubens Gisbert; Spitz, Mariana; Silva, Sônia Maria César Azevedo; Colletta, Marcus Vinicius Della (Arquivos de Neuro-Psiquiatria, 2022)
The treatment of Parkinson's disease (PD) is challenging, especially since it is considered highly individualized. The Brazilian Academy of Neurology has recognized the need to disseminate knowledge about the management of PD treatment, adapting the best evidence to the Brazilian reality. Thus, the main published treatment guidelines were reviewed based on the recommendations of group from the Movement Disorders Scientific Department of the Brazilian Academy of Neurology.
Keywords: Parkinson Disease; Antiparkinson Agents; Deep Brain Stimulation; Rehabilitation